100 years of rising corporate concentration - Spencer Y. Kwon; Yueran Ma; Kaspar Zimmermann (Leibniz Institute for Financial Research SAFE, 2022)
We collect data on the size distribution of all U.S. corporate businesses for 100 years. We document that corporate concentration (e.g., asset share or sales share of the top 1%) has increased persistently over the past century. Rising concentration was stronger in manufacturing and mining before the 1970s, and stronger in services, retail, and wholesale after the 1970s. Furthermore, rising concentration in an industry aligns closely with investment intensity in research and development and information technology. Industries with higher increases in concentration also exhibit higher output growth. The long-run trends of rising corporate concentration indicate increasingly stronger economies of scale.
Keywords: E23; E01; N12; 330; Corporate concentration; economies of scale